The Influence of Financial and Non-Financial Factors on Regional Government Financial Performance: Literature Review Study - Rustam; Hetami, Adietya Arie (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
It is hoped that the construction of public facilities and infrastructure will open up accessibility and facilitate community activities, especially those related to the economy, which will be able to improve regional financial performance and good decentralization capabilities. The aim of this research is to look at regional financial capabilities to grow independently to regulate and increase regional financial potential both through financial and non-financial means. This research is a literature study that reviews 40 scientific articles related to financial performance from 2018 to 2023 using a descriptive analysis approach. The findings from this research show that in relation to the implementation of regional financial progress, the variables of regional original income and regional head competence have an influence on financial performance. Meanwhile, for several variables such as: balancing funds, opinions on regional financial performance reports and capital expenditure. Regarding capital expenditure, the government needs to pay attention to appropriate and in-depth analysis to determine funds that are capable of providing prosperity to the region so that it will be able to have a positive impact on regional finances.